1982
DOI: 10.1172/jci110437
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a human neutrophil angiotension II-generating protease as cathepsin G.

Abstract: A B S T R A C T A human neutrophil protease, initially termed neutral peptide-generating protease, has been shown to cleave angiotensin II directly from angiotensinogen and has been identified as leukocyte cathepsin G. When purified neutrophils were disrupted by nitrogen cavitation and fractionated by differential centrifugation, 44 and 24% of the angiotensin II-generating activity was in the lysosomal and undisrupted cell fractions, respectively. Cytochalasin B-treated human neutrophils stimulated with N-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
3

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 33 publications
0
45
0
3
Order By: Relevance
“…It has been suggested that cathepsin G may play a role in the development of hypertension, based on its ability to convert both angiotensinogen [15] and angiotensin I [16] directly to angiotensin 11. Human cathepsin G has also been reported to cleave myosin and thus may be involved in muscle catabolism [17].…”
mentioning
confidence: 99%
“…It has been suggested that cathepsin G may play a role in the development of hypertension, based on its ability to convert both angiotensinogen [15] and angiotensin I [16] directly to angiotensin 11. Human cathepsin G has also been reported to cleave myosin and thus may be involved in muscle catabolism [17].…”
mentioning
confidence: 99%
“…In 1974, Boucher, Asselin, and Genest 37 reported the first biochemical description of an alternative pathway to that of ACE for Ang II formation via tonin in the rat salivary gland. From 1976 to 1982, other reports of alternate Ang II forming enzymes included trypsin, 38 kallikrein, 39 and cathepsin-G. 40 Tonin, tissue plasminogen activator, and elastase were reported to generate Ang II either from angiotensinogen or Ang I. 41 Physiological evidence for the presence of alternative Ang II-forming mechanisms to ACE was first reported by Cornish, Joyner, and Gilmore in 1976.…”
Section: Non-standard Abbreviations and Acronymsmentioning
confidence: 99%
“…On the other hand, infiltration of inflammatory cells also could contribute to the local generation of angiotensin II during AP. It has been reported that neutrophil expresses cathepsin G on their membrane, which could actively convert angiotensinogen to angiotensin II (Tonnesen et al, 1982). Neutrophil could also promote angiotensin II generation via activation of prorenin (Dzau et al, 1987).…”
Section: Redox-sensitive Erk-induced Pancreatic Inflammation 453mentioning
confidence: 99%